Effects of varying copper concentrations on photosynthesis of gracilaria salicornia and padina sanctae-crusis - Aaron, Jesrelljane J.; Dy, Danilo T. (2016)
Two tropical macroalgae, gracilaria salicornia and padina sanctae-crusis, were exposed to varying concentrations of total Cu and subsequently subjected to photosynthesis -irradiance (P-I) response experiments. The study aimed to determined the effects of total Cu toxiticy on the P-I model parameters and growth rate of the macroalgae. The photosynthetic efficiency (a) showed a decreasing pattern with increasing total Cu concentration. Light saturation (lk) for both algae increased at lower concentration and showed transient shift at 12.5 ug total Cu L-1. The maximum photosynthesis (Pmax) of P. sanctae-crusis was higher in specimens expoed to 12.5-25 ug total Cu-1 compared to the controls. Unlike P. sanctae-crusis, G. salicornia exposed to total Cu-free medium as well as those at12.5-25 ug total Cu L-1 were comparable. But, both algae showed decreasing Pmax values from 50-500 ug total Cu L-1. Respiration (R) showed non-linear pattern due to some delay of the effect of copper on the respiratory system. Growth data proved to be more sensitive to total Cu with the reductions of mean daily growth rate starting at 12.5 ug total Cu L-1 for G. salicornia and negative growth rate at 500 ug total Cu L-1 for P. sanctae crusis. After 7 days of exposure the EC20 for G. salicornia and P. sanctae-crusis were 100 and 50 ug total Cu L-1., respectively. The results suggested severe impact of total Cu+ at high concentrations on P-I parameters and growth rate of G. salicornia and P. sactae-crusis.
Keywords: Physiological effects of copper